Vascularized composite allotransplantation – a Council of Europe position paper. (26th November 2018) - Thuong, Marie; Petruzzo, Palmina; Landin, Luis; Mahillo, Beatriz; Kay, Simon; Testelin, Sylvie; Jablecki, Jerzy; Laouabdia‐Sellami, Karim; Lopez‐Fraga, Marta; Dominguez‐Gil, Beatriz
Summary: After more than 120 hand‐upper extremity and 37 face transplant procedures performed worldwide, vascularized composite allotransplantation (VCA) now falls under the scope of organ transplant legislation in Europe and the United States. While in the USA, VCA has been considered as standard care since 2014, VCA in Europe is still performed through clinical research trials, except in United Kingdom. However, after two decades of favourable experience with upper extremity transplantation (UET), professionals in Europe are proposing hand allotransplantation as "controlled standard" care, as opposed to face transplantation (FT), which is still a challenging activity. The European Committee on Organ Transplantation (CD‐P‐TO) has elaborated a position paper to provide recommendations concerning regulatory aspects for UET and FT. It is aimed at Health Authorities in charge of the oversight – and coordination – of organ donation and transplantation, and at professional groups to help them manage such complex and costly programs dedicated to properly selected patients.